2019
DOI: 10.1080/13561820.2019.1676209
|View full text |Cite
|
Sign up to set email alerts
|

Towards a theoretical framework for Integrated Team Leadership (IgTL)

Abstract: This study presents a framework for the leadership of integrated, interprofessional health, and social-care teams (IgTs) based on a previous literature review and a qualitative study. The theoretical framework for Integrated Team Leadership (IgTL) is based on contributions from 15 professional and nonprofessional staff, in 8 community teams in the United Kingdom. Participants shared their perceptions of IgT's good practice in relation to patient outcomes. There were two clear elements, Person-focused and Task-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…• Considered as hierarchal leadership style, where leaders use their charisma to motivate individuals to achieve more than expected and look beyond self-interest (Nieuwboer et al, 2019) In the context of health, it is considered as more leaders centric approach and often linked with the directive style of leadership (Orchard and Rykhoff, 2015) *These three leadership behaviors are conceptually distinct but the way they are described in the literature seems to have more similarities (Smith, et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…• Considered as hierarchal leadership style, where leaders use their charisma to motivate individuals to achieve more than expected and look beyond self-interest (Nieuwboer et al, 2019) In the context of health, it is considered as more leaders centric approach and often linked with the directive style of leadership (Orchard and Rykhoff, 2015) *These three leadership behaviors are conceptually distinct but the way they are described in the literature seems to have more similarities (Smith, et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that the successful implementation of integrated care has improved certain patient outcomes, such as hospital admission rates, length of hospital stay and patient satisfaction 52 53. It can therefore be inferred that strong leadership in IHSs is extremely valuable in the delivery of high quality healthcare to patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has reported that neither paying clinicians to do more in care homes nor investing in training is sufficient to achieve better outcomes for residents (Goodman et al, 2016 ). It is now well accepted that integrated person‐centred care depends on excellent team leadership (Kim et al., 2017 ; Smith et al., 2020 ; Warwick‐Giles & Checkland, 2018 ) and a strategic commitment to integrated cross sector provision (Atwal & Caldwell, 2002 ). Furthermore, existing relationships which build trust between practitioners are found to support effective working (Gordon et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%